-66=6(z-9)

Simple and best practice solution for -66=6(z-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -66=6(z-9) equation:



-66=6(z-9)
We move all terms to the left:
-66-(6(z-9))=0
We calculate terms in parentheses: -(6(z-9)), so:
6(z-9)
We multiply parentheses
6z-54
Back to the equation:
-(6z-54)
We get rid of parentheses
-6z+54-66=0
We add all the numbers together, and all the variables
-6z-12=0
We move all terms containing z to the left, all other terms to the right
-6z=12
z=12/-6
z=-2

See similar equations:

| 55=6f+19 | | (6x+12)=(4x+20) | | 3x-25+2×=50 | | 34=t/6+25 | | 2-9x+-18=5x-15+15 | | 2+3x=12x-6 | | 4=n-59/10 | | x+11,7=25,4 | | 3/5+2x=0 | | (4x+10)=(3x+20) | | m/11=5 | | 2w-24=62 | | 180=14x+20 | | 2+18/v=11 | | j/4-10=13 | | 0.4x-7=-0.3x+2.8 | | -9(2-2x)-10(10-4x)=2-5-2x | | 2x+x+4/5=4 | | 0.16(p+24)=10 | | 2x+5x-4=12x-8+4 | | 15•0+9y=90 | | 11+3b=20 | | 3(6x-6)=30x | | 1/3(9-3x)=-4 | | 0.4x-7=0.3+2.8 | | 11d(2)=22d | | 88=8(q+3) | | 4(x-4)+5x=6x+3(x-6) | | 8(x=3)=12x-4 | | 3(8-2x)=6(3x-2) | | (2y+3)3y=8 | | 9-(2+3x)=x-17 |

Equations solver categories